MEWUJUDKAN LOYALITAS MELALUI PEMENUHAN HARAPAN PELANGGAN - Abdillah, Yusri (FIA UB, 2007)
Basically, brand has strategic position in determining a company success. The company must has business strategy in order to offend new customers and to defend present customers. It can be doneby increasing market, capturing market share, building barriers switching and increasing customer satisfaction. Nowadays, customer satisfaction become main goal of modern company. For creatingÂ and preserving a company success, they must keep innovation continually and give big attention to customer by applying high service quality